Optimized Strengthening Based on Concrete Jacketing for Minimum Eccentricity - Mitropoulou, Chara Ch.; Naziris, Iordanis A.; Kallioras, Nikos Ath.; Lagaros, Nikos D. (Frontiers in Built Environment, 2022)
The coupled lateral-torsional response is observed in building structures subjected to dynamic excitation due to lack of symmetry in terms of mass/stiffness in any of the stories’ plan views; such structural systems are called eccentric. Much damage and even collapse are concerned with building structures with asymmetric plan views. Combined torsional-translational vibration of their structural system results in higher ductility demands, especially to vertical structural elements located at the perimeter of the plan view. This study examines the minimization problem of the torsional response of an eccentric, multi-story reinforced concrete (RC) building by strengthening its vertical structural elements with RC jackets. The problem of minimizing the eccentricity between mass and rigidity centers for all story layouts and the corresponding minimization problem of the eccentricity between mass and strength centers for all stories are considered two separate formulations for the reduction of the torsional response optimization problem. Based on recent studies, the center of strength is preferable for assessing the torsional response of buildings in case of inelastic response. The imperialist competitive algorithm (ICA), a member of the family of evolutionary search algorithms, is used to solve the two optimization problems. The optimization problems are formulated for the case study building considered after assessing its structural behavior and capacity through nonlinear static analyses before and after strengthening. The later process was implemented to meet code requirements and examine the improvements achieved through optimization.